Tenascin‐C in brain injuries and edema after subarachnoid hemorrhage: Findings from basic and clinical studies. Issue 1 (22nd September 2018) - Suzuki, Hidenori; Fujimoto, Masashi; Kawakita, Fumihiro; Liu, Lei; Nakatsuka, Yoshinari; Nakano, Fumi; Nishikawa, Hirofumi; Okada, Takeshi; Kanamaru, Hideki; Imanaka‐Yoshida, Kyoko; Yoshida, Toshimichi; Shiba, Masato
Abstract: Subarachnoid hemorrhage (SAH) by a rupture of cerebral aneurysms remains the most devastating cerebrovascular disease. Early brain injury (EBI) is increasingly recognized to be the primary determinant for poor outcomes, and also considered to cause delayed cerebral ischemia (DCI) after SAH. Both clinical and experimental literatures emphasize the impact of global cerebral edema in EBI as negative prognostic and direct pathological factors. The nature of the global cerebral edema is a mixture of cytotoxic and vasogenic edema, both of which may be caused by post‐SAH induction of tenascin‐C (TNC) that is an inducible, non‐structural, secreted and multifunctional matricellular protein. Experimental SAH induces TNC in brain parenchyma in rats and mice. TNC knockout suppressed EBI in terms of brain edema, blood‐brain barrier disruption, neuronal apoptosis and neuroinflammation, associated with the inhibition of post‐SAH activation of mitogen‐activated protein kinases and nuclear factor‐kappa B in mice. In a clinical setting, more severe SAH increases more TNC in cerebrospinal fluid and peripheral blood, which could be a surrogate marker of EBI and predict DCI development and outcomes. In addition, cilostazol, a selective inhibitor of phosphodiesterase type III that is a clinically available anti‐platelet agent and is known to suppress TNC induction, dose‐dependently inhibited delayed cerebral infarction and improved outcomes in a pilot clinical study. Thus, further studies may facilitate application of TNC as biomarkers for non‐invasive diagnosis or assessment of EBI and DCI, and lead to development of a molecular target drug against TNC, contributing to the improvement of post‐SAH outcomes.